(untitled) (The Journal of Building and Land Development, 2018)
Although planning education has been implemented in Zambia since 1972, many believe that it has had little impact on improving the physical, social and economic environment in rural and urban areas Planning graduates are produced merely to fill positions mainly in central and local government authorities and not to play an active role in the development of the nation. It is for this reason that there is need to critically analyse the genealogy, development and current and future role of planning education in national development processes. This paper is a contribution to the broad debate on how to revitalise planning education in Africa and particularly in Zambia. It highlights the national context in which planning education is implemented, the key issues influencing urban and regional planning, and the Zambian planning system. The paper then focuses on the planning education system in Zambia and how this system has failed to meet the planning needs of Zambian society and concludes with practical suggestions on revitalising planning education to make these more responsive to the needs of the people. It concludes with a suggestion for an organisational assessment and strategic planning exercise to sharpen the vision and focus of planning education and for the planning department to strengthen linkages and networks with local and international institutions.